2014
DOI: 10.5539/ies.v7n13p271
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Trainees’ Strategies for Managing the Behaviours of Students with Special Needs

Abstract: This study aimed to determine how a group of teacher trainees handled challenging behaviour by students during teaching practice. A total of 35 teacher trainees from the special education programme of a local university were chosen as respondents. A questionnaire based on a 5-point Likert-type scale was administered in this study. The data were analysed descriptively involving frequencies and percentages, mean scores and standard deviations. The results showed that the most frequent types of challenging behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In addition, a previous study found that teachers' sense of self-efficacy can be influenced by the preparation that they receive when developing their skills and knowledge [8,9]. Therefore, this research further examined the influence of a teacher's professional learning on their self-efficacy.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, a previous study found that teachers' sense of self-efficacy can be influenced by the preparation that they receive when developing their skills and knowledge [8,9]. Therefore, this research further examined the influence of a teacher's professional learning on their self-efficacy.…”
Section: Introductionmentioning
confidence: 92%
“…Successful classroom management can effectively minimise student misconduct and intervene with negative student behaviour when it happens [8,21]. In classroom behaviour management, teachers are involved in several tasks, such as managing students' activities, creating a productive environment, and employing effective techniques to address students' challenging behaviour [22].…”
Section: Verbal Persuasionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such concerns arise from the assumption that individualized instruction (e.g., small group instruction by learning support assistants) for students with special needs distracts students not in need of additional support (Rose & Coles, 2002). There are also concerns about noise related to disruptive behaviour of students with emotional and behavioural difficulties in inclusive education classrooms (Ali et al, 2014). Self-stimulating sounds (e.g., humming) from autistic students educated in inclusive classrooms can also be perceived as annoying by other students (Wood, 2020).…”
Section: Classroom Noise and Academic Performancementioning
confidence: 99%